Análise ergonômica de uma fábrica de carroceria de caminhão - Reis, Karollayne Menezes (2017)
An ergonomics and study of the adaptation of work to man relating the development of his tasks as characteristics of the worker. Másculo e Vidal (2011 apud CRUZ et al., 2015), affirm that the OWAS tool is a simple method for posture analysis evaluating the positioning of the trunk, arms and legs of the worker, in addition to considering the loads and efforts during the accomplishment of their activities. The present article aimed the realization of an Ergonomic Analysis of Work (EWA) analyzing the conditions of the work environment in a truck body factory. The data were obtained through photographs, filming and observations in loco in the production process of the manufacture of a body. The following steps can be evaluated: wood preparation, hardware, assembly and painting, and its sub-stages, in order to detect ergonomic risks and to recommend solutions based on the results obtained. In these jobs, employees are exposed to excessive noise, over 90 dB, have incorrect postures, perform repetitive movements and are not instructed to use PPE. The data obtained in this research can serve as suggestions and recommendations to improve the jobs of the company analyzed, aiming at improving the health of the worker.